Morphological indicators of structural control, relative sea-level fluctuations and platform drowning on present-day and Miocene carbonate platforms - Menier, D. (Elsevier Ltd, 2014)
The morphology of Carbonate platforms may be influenced by tectonic activity and eustatic variations. 3D seismic data and satellite imagery are used in order to investigate the morphological similarities between present-day carbonates platforms, East of Borneo Island and Miocene carbonate platforms of the South China Sea. The morphological similarities exhibit platform fragmentation, that could be caused by subtle faulting, sufficient to drown reef rims; platform contraction, which is a result of back-stepping of the reef margin during a relative sea level rise and polygonal patterns in internal lagoons, described as mesh reefs in modern platforms and possibly interpreted as karst in Miocene platforms.Vertical movements may trigger the formation of new geomorphological conditions that modify the distribution of coral growth with respect to the new hydrodynamic conditions in space and time. These movements (uplift and tilting) reduce and localize the space necessary for the coral ecosystem, explaining the contraction leading to drowning of parts of and, ultimately, the whole platform. Â© 2014.